Principles of Practical Training Organization in a Networking (Development of the Module "Psychological Prevention of Behavioral Disorders and Abnormalities in Development" as Example) - Bogdanovich, N.V.; Delibalt, V.V.; Chernushevich, V.A. (Psihologiâ i pravo, 2015)
The article presents principles of inserting study subjects and practices in educational modules running with network organizations (internship sites). We proposed a methodological basis of the modular organization of educational process in the framework of the master's program, combied the activity, competence and psychotechnical approaches. Networking of leading chair and specially selected organizations providing the base for practical training solves the problem of organizing activity-related content of educational module. We discussed the main options for networking with the databases of practice and offered methodological principles of designing the educational practice-oriented module, wherein the main principle is the reflexive and activity character of networking. We proposed activity-based content of educational module "Psychological prevention of behavioral disorders and abnormalities in development", based on the substantial psychological definition of psychoprophylaxis as a directions of professional activity of the psychologist. Рассмотрены принципы интеграции учебных предметов и практик в учебные модули, реализуемые с участием сетевых организаций (стажировочных площадок). Предложены методологические основания модульной организации учебного процесса в рамках магистерской программы. При этом синтезируется деятельностный, компетентностный и психотехнический подходы. Сетевое взаимодействие ведущей кафедры со специально отобранными базовыми организациями практики решает проблему деятельностной организации содержания модульной подготовки. Рассматриваются основные варианты сетевого взаимодействия с базами практики, предлагаются методические принципы построения учебного модуля практико-ориентированной подготовки, основной из которых – рефлексивно-деятельностный характер сетевого взаимодействия. Предложено деятельностное содержание учебного модуля «Психологическая профилактика нарушений поведения и отклонений в развитии», основанное на содержательном психологическом определении психопрофилактики как направления профессиональной деятельности психолога.